Financial Development Strategies of Countries: Identifying Priority Financial Instruments - Gospodarchuk, Galina; Zeleneva, Elena (Emerging Science Journal, 2024)
The effectiveness of financial development strategies for countries depends on the methodology used for their formation and implementation. However, a review of the literature reveals that the methodology for implementing these strategies is not fully developed. Therefore, this study aimed to create a methodology for implementing financial development strategies by identifying priority financial instruments. The study utilized rule-based judgment, iterative methods, and the "GAP" method. As a result, the "5S+" concept was developed—an expanded version of the "5S" concept. The novelty of the "5S+" concept lies in its inclusion of financial instruments, as well as the rules and methods for determining priority financial instruments. This is the first time such a modification of the "5S" concept is proposed. The "5S+" concept was tested using data from the UK for 2007-2022. The test results allowed us to determine the UK's strategic financial development goals for 2023-2025 and identify priority financial instruments necessary to achieve these goals across the board. The expanded "5S" concept is highly representative, objective, and broadly applicable. It enhances the existing methodology for strategic financial development management and introduces new opportunities for improving the quality of strategic policy documents. Doi: 10.28991/ESJ-2024-08-06-06 Full Text: PDF